How to cheat in Adobe Flash CS6 : the art of design and animation - Georgenes, Chris (Burlington, MA : Focal Press, 2013)
'Whether you are creating an animated short, catchy and fun cartoon or mobile game, save time and money with expert cheats by renowned Flash Expert, Chris Georgenes with all new content for the Flash CS6 revision. With practical applications and step by step tutorials solve problems quickly to develop creative projects to time and to budget. Many of these walkthroughs are real-world client projects, with the source files supplied for you to open and explore. With these real-life professional projects you'll discover how to: bring objects to life with cool motion effects, make it rain, snow or set your world ablaze, develop flash mobile applications and many more tips and tricks not found anywhere else! With his in-depth knowledge of the little-known secrets used by the pros to produce creative, professional animations, Chris is the go-to guru for designers and animators who want to create great animation, applications or motion design with Flash. Fully updated for CS6, How to Cheat in Flash CS6, is a goldmine of artistic inspiration, timesaving practical tips, tricks and step-by-step walkthroughs that you'll wonder how you survived without it. New! CS6 cheats and examples with practical solutions for the busy animator with a focus on Action Script, Flash for mobile applications, specifically for Android development, as well as a focus on an improved physics engine. Put the Adobe Flash CS6 cheats to the test with the fully updated companion website with downloadable Flash source files, examples and video tutorials, and a creative commons game, developed with Adobe, to demonstrate the new functionality of CS6!'--
'Learn the art of animation and design in just a matter of minutes. Why take months to learn every button in Adobe Flash when you can create great visuals with just a few key tools? Chris Georgenes is your go-to guru for creating great animation, bringing objects to life with cool motion effects, and even enhancing your productivity and toolkit with new plugins--all in Flash! How to Cheat in Flash CS6 is a goldmine of artistic inspiration, time-saving practical tips, tricks and step-by-step walkthroughs; you'll wonder how you ever worked in Flash before this book. Make it rain, snow, or set your world ablaze with real-world client projects and project source files. Includes all NEW content and cheats on Sprite Sheet generator and CreateJS extension. - Work over the shoulder of a renowned Flash expert, and apply the practical techniques, tips and tricks to your own projects with downloadable Flash source files, examples and tutorials all available at www.howtocheatinflash.com - Learn a myriad of tricks based on real-life working methods to helk you work faster and more efficiently, with NEW content specific to CS6. - Work from the problem to the solution, to gain the best possible results from Flash. Chris Georgenes is the Art and Animation Director and founder of Mudbubble LLC. He spent the better part of the last decasde designing and animating for the Web, games, and television. His clients include Adobe, Macromedia, Yahoo!, Digitas, Hasbro, Ogilvy and AOL to name a few. Chris is also a course author and instructor for sessions.edu'--
Includes indexs.
Keywords: Flash (Computer file).; Computer animation; Digital cinematography